Small Bowel Review - Part II - ABR Thomson; E Jarocka-Cyrta; J Faria; GE Wild (Canadian Journal of Gastroenterology)
The small bowel has undergone intense study. Part II of this review of the small bowel summarizes the current knowledge about the permeability of the gastrointestinal epithelium; the brush border membrane; motility; carbohydrates; diabetes; ethanol; diet; and diagnostic procedures.